Laws that Protect Florida’s Wildlife - Joe Schaefer; John Tucker; Maia McGuire (EDIS)
Endangered species are not the only wildlife protected by the legal system. All of Florida’s wildlife is more or less safeguarded by a variety of laws. Laws addressing wildlife can be found at the federal, state, regional, and local levels of government. Wildlife protection may also take the form of conventions, treaties, and executive orders. All are subject to periodic change. For example, legislators can alter or delete laws every year. This revised 5-page fact sheet summarizes federal laws and state statutes and rules. Written by Joe Schaefer, John Tucker, and Maia McGuire, and published by the UF Department of Wildlife Ecology and Conservation, February 2012.